Linear Codes and Self-Polarity - Iliya Bouyukliev; Stefka Bouyuklieva; Mariya Dzhumalieva-Stoeva; Dushan Bikov (Mathematics)
This work studies projective self-dual (PSD) and self-polar linear codes over finite fields with q elements, where q is a power of a prime. The possible parameters for which PSD codes may exist are presented, and many examples are provided. Algorithms for checking whether a q-ary linear code is self-polar are described. Many PSD and self-polar codes over fields with two, three, four, and five elements with two and three nonzero weights are constructed.